Song Movement as a Learning Medium: Shape Analysis, MI Mapping, and Teachers' Creative Process at Pertiwi Kutoharjo Kaliwungu Kindergarten - Purhanudin, Viktor; Wulandari, Dewi; Purnomo, Try Wahyu (Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to describe the form of song movement created by Pertiwi Kutoharjo Kaliwungu Kindergarten Teacher, map the elements of song movement to the stimulation of Multiple Intelligences (MI), and explain the creative process of teachers along with the supporting factors and challenges of their implementation at Pertiwi Kutoharjo Kaliwungu Kindergarten. The approach used is descriptive qualitative with a focus on case studies. Data was collected through observation of the implementation of activities, field notes, and study of video documents. The analysis was carried out by summarizing the structure of the musical form and choreography, mapping the MI indicators that appeared during the activity, and then interpreting the findings based on the implementation in the classroom. The results of the study showed that there were three movements of songs created that were used as learning media, namely